2006
DOI: 10.1136/jnnp.2006.108761
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that congenital hydrocephalus is a precursor to idiopathic normal pressure hydrocephalus in only a subset of patients

Abstract: Objective: To identify the proportion of patients in a large idiopathic normal pressure hydrocephalus (INPH) cohort with large head circumference (HC) who presumably have congenital hydrocephalus that has not become clinically apparent until late in life. Methods: HC was measured in 158 patients diagnosed with communicating INPH and assigned to HC centile range adjusted for height and sex. The proportion of patients with INPH and HC above the 97th, 90th or 50th centiles was compared with the proportion expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…The Tinetti assessment tool revealed a balance score of 9/16 and a gait score of 6/12 for a total score of 15/28, which is consistent with an increased risk of falling [Tinetti, 1986]. His head circumference was 61.5 cm, which exceeded the 97th centile for an adult man of his height [Bushby et al, 1992], which is consistent with the diagnosis of congenital hydrocephalus with late decompensation [Wilson and Williams, 2007]. A brain MRI done 2 weeks before this evaluation revealed enlarged ventricles with a frontal horn span of 5.1-5.5 cm, a third ventricle span of 11-15 mm, and a patent Sylvian aqueduct.…”
Section: Clinical Descriptionsupporting
confidence: 63%
“…The Tinetti assessment tool revealed a balance score of 9/16 and a gait score of 6/12 for a total score of 15/28, which is consistent with an increased risk of falling [Tinetti, 1986]. His head circumference was 61.5 cm, which exceeded the 97th centile for an adult man of his height [Bushby et al, 1992], which is consistent with the diagnosis of congenital hydrocephalus with late decompensation [Wilson and Williams, 2007]. A brain MRI done 2 weeks before this evaluation revealed enlarged ventricles with a frontal horn span of 5.1-5.5 cm, a third ventricle span of 11-15 mm, and a patent Sylvian aqueduct.…”
Section: Clinical Descriptionsupporting
confidence: 63%
“…To minimize heterogeneity and ethnic influences that may affect morphometric parameters such as height and thus HC, only Spaniards whose family had no known history of immigration to Spain were included in this study to obtain a sample that was geographically representative of the country. Additional inclusion criteria were as follows: (1) age equal or greater than 17 years, (2) mTBI with no loss of consciousness, (3) normal neurological examination results and Glasgow coma scale score of 15, (4) normal CT scans, (5) subjects who were born fullterm with normal neurodevelopment, (6) no previous history of neurological or psychiatric pathology, (7) no previous history of TBI, (8) no previous history of alcoholism or drug addiction, and (9) willingness to participate in the study. Patients with cranial contusion that might have hampered HC measurements and those who did not meet the inclusion criteria were excluded.…”
Section: Patient Selection Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…Hydrocephalus associated with severe ventriculomegaly and macrocephaly may be caused in the early stages of life, although symptoms may occur during adulthood [6][7][8][9]. The presentation of this syndrome may be very similar to "normal pressure" hydrocephalus (Hakim and Adams syndrome), however, the prognosis may be worse [5], with less improvement and a greater rate of complications.…”
Section: Indications Of Assessing Head Circumference Clinical Applicmentioning
confidence: 99%
See 1 more Smart Citation
“…As Oi's study include three normocephalic and one unknown status patients as stated above, the authors questioned macrocephaly may not an absolutely necessary condition to diagnose this entity and tried to find the real incidence in this population. In similar context, Wilson and Williams 17) reported that a significantly larger proportion of patients with idiopathic normal pressure hydrocephalus (iNPH) have a head circumference greater than the 90th or 97th percentile than normal population. But they concluded that compensated congenital hydrocephalus is just one etiology of iNPH but not all.…”
mentioning
confidence: 96%